Necessity and Opportunity for Customer‐Prescribed Outage Notifications. Issue 10 (May 2015) - Myers, Robert
<x xml:space="preserve">Abstract</x> Today, Internet users in the United States spend an average of 42 minutes on Facebook, 21 minutes on Instagram, and 17 minutes on Twitter each day (see Exhibit 1).